Suśrutasaṃhitā Kalpasthānam : Uttaratantre Śālākyatantrāt Kaumārabhrtyaparyyantañca - Suśruta (Satyayantre, 1917)
Treatise, with Suśrutārthasandīpana commentary, on ayurvedic system in Indic medicine.